Pemberdayaan UMKM melalui pemanfaatan limbah kulit durian dan studi kelayakan usaha di ervin duren Jepara - Triwibowo, Bayu; Prasetiawan, Haniif; Rahardjo, Teguh Hardi (STAI Auliaurrasyidin Tembilahan, 2025)
Durian peel waste in Ervin Duren, Jepara, has not been optimally utilized, despite its large amount and potential to pollute the environment. Therefore, this community service activity was conducted to empower local MSMEs through training in making candles from durian peel waste and business feasibility studies. The primary objective of this activity was to enhance product innovation skills and managerial capabilities of small business owners in the village. The method used in this activity involved hands-on training and group discussions to deepen participants' understanding of waste processing and business planning. The results show that participants successfully processed durian peel waste into quality candles, with approximately 75% of participants starting production. Additionally, participants’ understanding of business feasibility aspects significantly improved, particularly in market analysis and financial planning. This activity positively impacted the local economy while encouraging waste reduction in the environment. Overall, this community service demonstrated that product innovation and business management training can increase the competitiveness of local MSMEs and provide sustainable solutions for environmental issues.